“Good Grief! It’s a Men’s Group, Charlie Brown” - Buitenbos, Peter (Canadian Journal of Counselling and Psychotherapy, 2012)
This article uses autoethnography as a methodological approach to explore practical issues for counselling men in a group setting. A narrative was constructed that engages the reader in my experience at a therapeutic workshop for men. The narrative is interwoven with analysis that draws on research about masculinity. I use reflexivity to disclose my motivation and decision to attend the workshop and examine steps taken to create a safe and inclusive environment for participants. The article explores the conditions under which men are likely to participate in a vulnerable dialogue with other men. I note that this approach of “men helping men” can have lasting value for participants, leading to the development of close personal bonds with other men.